2021
DOI: 10.1186/s13256-021-02775-9
|View full text |Cite|
|
Sign up to set email alerts
|

Clear-cell carcinoma originating from cesarean section scar: two case reports 

Abstract: Background Clear-cell carcinoma arising from the surgical cesarean section scar is very infrequent. The present study reports two patients with clear-cell carcinoma arising from an abdominal wall scar 20 and 23 years after their last cesarean section. Case presentation Both Iranian patients had prior cesarean sections nearly 20 years earlier. Patients 1 and 2 had transverse and vertical abdominal incisions, respectively. The initial clinical presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The occurrence of endometriosis implants in surgical incisions is well-established in the literature, and cesarean scar endometriosis is the most common site of abdominal wall endometriosis ( Zhang et al, 2019 ). While CCC arising from abdominal incisions is rare, it has also been documented in the literature—and most commonly associated with prior cesarean section ( Hashemi et al, 2021 ). While there was no background endometriosis observed in any of the tumor specimen sent for pathologic evaluation, it is highly plausible that the tumor destroyed the endometriotic implant from which it arose.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of endometriosis implants in surgical incisions is well-established in the literature, and cesarean scar endometriosis is the most common site of abdominal wall endometriosis ( Zhang et al, 2019 ). While CCC arising from abdominal incisions is rare, it has also been documented in the literature—and most commonly associated with prior cesarean section ( Hashemi et al, 2021 ). While there was no background endometriosis observed in any of the tumor specimen sent for pathologic evaluation, it is highly plausible that the tumor destroyed the endometriotic implant from which it arose.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], the authors identified an error in the author name of Arezoo Esmailzadeh.…”
Section: Correction To: J Med Case Reports (2021) 15:146 Https://doiorg/101186/s13256-021-02775-9mentioning
confidence: 99%